Vitamin D Receptor (VDR) Allelic Variants Correlating with Response to Vitamin D3 Supplementation in Breast Cancer Survivors. (2nd January 2022) - Kazemian, Elham; Davoodi, Sayed Hossein; Akbari, Mohammad Esmaeil; Moradi, Nariman; Gharibzadeh, Safoora; Mondul, Alison M; Jamshidi-Naeini, Yasaman; Khademolmele, Maryam; Zarins, Katie R.; Ghodoosi, Nasim; Rozek, Laura S.; Amouzegar, Atieh
Abstract: We investigated how vitamin D receptor ( VDR ) allelic variants affect breast cancer survivors' responses to vitamin D3 supplementation to increase circulating 25-hydroxy vitamin D (25(OH)D) levels. Two hundred and fourteen patients who were diagnosed with breast cancer at least 6 mo, prior to the study and had completed all treatment regimens were assigned to consume 4000 IU of vitamin D3 daily for 12 weeks. Linear and multinomial logistic regression analyses were used to analyze the association of VDR single nucleotide polymorphism (SNPs) with changes in circulating 25(OH)D. The TaqI and BsmI VDR sequence variants modified the effect of vitamin D3 treatment on the plasma 25(OH)D changes ( P value = 0.008 for TaqI and P value = 0.0005 for BsmI). Patients with the bb [Q4 vs. Q1 odds ratio(OR) 8.04, 95% confidence interval (CI) 1.55–41.57] and tt [Q4 vs. Q1 OR 4.64 95%CI 1.02–21.02] genotype of BsmI and TaqI had larger increases in plasma 25(OH)D levels compared to those with BB and TT genotype respectively after adjustment for potential confounders. Haplotype analyses suggested the existence of specific combination of alleles that might be associated with circulating 25(OH)D changes. VDR allelic variants modulate vitamin D3 supplementation to increase plasma 25(OH) levels in breast cancer survivors.